(3GdSGej aj GdCSGejs - (3GdejOGfj GdfjSGHhQqi, CHh GdaVd, MeO Hf eMeO Hf CMeO Hf EHQGgje, (B815 (3g`s ((3eMeO UGdM GdCUagGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B.. (3aEf Gddg JYGdi GONQ dcd bQf aVjdI GJNPhgG Edi fHd efGge hSjdI hLYd GddGMb WGeMG HHUQ geJg Edi Ydh OQLI GdSGHb hSehb QJHJg ZjQ QGV HGdJNda Yf eVeGQg hEf cGf dG jOQc eKGQ ZHGQg (B...s
(3BNQgG (B:s
... (3ajdMb HbhGO GdgeI Edjg hef CQGO ChLH efg adjSa (B.. (3aj GdcSd Ydjg hef hdJgeG LejYG UaMI GdCYQGV aYfGf GeQg HjOjg hGddg GdeSJYGf hYdjg GdJcdGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\214s
(3cTa GdXfhf (B2\974s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GddZIs